The effect of moral material incentives on the job satisfaction of nurses in the Saudi health sector in government hospitals in the city of Riyadh - Jarrah, Ali Ahmed; Al-Mutairi, Sultan Musaed; Al-Farsi, Ali Abdo; Al-Otaibi, Farhan Tanf; Al-Muslim, Fadel Saleh; Al-Mutairi, Bassam MuJaab; Smaili, Ibrahim Ismail; Al-Fuhaid, Zikra Muhammad; Al-Otaibi, AbdulRahman Abbas (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the reality of material and moral incentives, and the level of job satisfaction in the Saudi health sector in government hospitals in the city of Riyadh. The study sample included a number of nurses in government hospitals in the city of Riyadh, who numbered (281) individuals. The questionnaire was used as a tool for data collection, and the study reached a number of results, the most important of which is that the responses of the study members about the level of job satisfaction for workers in the Saudi health sector in government hospitals in Riyadh with a mean of (3.68), where the averages of their approval of the challenges ranged between (4.16 to 3.35). ), which are averages located in the fourth and third category of the five-scale categories, which indicate (agree - neutral) on the study tool, and there are statistically significant differences, as it showed the presence of a positive statistically significant effect between material and moral incentives and job satisfaction for nurses in the Saudi health sector. in government hospitals in Riyadh. In light of the results, the study recommends that government hospitals in Riyadh should adopt the use of incentives in all its dimensions (material and moral) as they are an important element of stability, and given the direct or indirect increase in production and the result of job satisfaction. The administration of government hospitals in Riyadh must involve nurses in decision-making processes.
Keywords: Material Incentives; Moral Incentives; Job Satisfaction; Nurses; The Saudi Health Sector; Hospitals in Riyadh